Pengaruh Electronic-Word of Mouth pada Media Sosial Instagram dan Citra Destinasi terhadap Keputusan Pembelian (Survei pada Pengunjung Objek Wisata Kemuning Sky Hills) - Murti, Nova Wisnu; Riyanto, Buddy; Itasari, Andri Astuti (Jurnal Publisitas, 2024)
In the tourism industry, integrated marketing communications via Instagram plays an important role in influencing consumer purchasing decisions. This communication includes word of mouth information using electronic media (e-WOM) and other factors, such as destination image. This research was prepared and researched to see and find out whether Electronic Word of Mouth (e-WOM) on Instagram social media and destination image influence tourists' purchasing choices at Kemuning Sky Hills. The preparation of this scientific work was carried out using multiple linear regression model analysis using explanatory methods and using a quantitative approach. The object of this research is the Kemuning Sky Hills tourist attraction with visitors to the Kemuning Sky Hills tourist attraction who use Instagram social media as research subjects. The testing method used in this study is non-probability sampling, namely the Accidental Sampling type of testing. Important information was collected by distributing surveys to 96 respondents. From the final results of the research, a statement was obtained where E-WOM and destination image influenced purchasing choices with a significance result of 0.000 (p<0.05). Meanwhile, the t-count of e-WOM on purchasing decisions is 4.772 and the p-value is 0.000 (p<0.05). On the other hand, a t-value of 6.492 was obtained from the destination image variable and a p-value of 0.000 (p<0.05). The F-count for the simultaneous test in this study was 56.275 and the p-value was 0.000 (p<0.05). Therefore, the speculations H1, H2, and H3 can be accepted and acknowledged, namely that e-WOM and destination image have an impact or influence of 53.8% on purchasing decisions.